2021
DOI: 10.20473/spmrj.v3i2.25169
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Knee Injury in East Java’s Puslatda Fencing Athletes

Abstract: Background: Fencing is one of many sports that are held in major sports events, both nationally and internationally. Fencing also has a high risk of injury, and knee injury is the most common injury site according to the authors' observations. Even so, studies on knee injuries in fencing athletes are very scarce, especially in Indonesia.Aim: To ascertain the prevalence of knee injuries and its intrinsic risk profile in fencing athletes at East Java Puslatda (regional training center).Material and Methods: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(18 reference statements)
0
0
0
1
Order By: Relevance
“…Kemampuan merubah arah sangat penting dilakukan dalam olahraga multidirectional. Perubahan arah atau change of direction (COD) sering dilakukan pada olahraga sepakbola, basket, american football, bisbol atau softball dan sebagainya (Young, Dawson, and Henry, 2015). Dalam olahraga softball COD dilakukan untuk menghindar dan mencetak skor, (Nimphius et al, 2016).…”
Section: Introductionunclassified
“…Kemampuan merubah arah sangat penting dilakukan dalam olahraga multidirectional. Perubahan arah atau change of direction (COD) sering dilakukan pada olahraga sepakbola, basket, american football, bisbol atau softball dan sebagainya (Young, Dawson, and Henry, 2015). Dalam olahraga softball COD dilakukan untuk menghindar dan mencetak skor, (Nimphius et al, 2016).…”
Section: Introductionunclassified
“…According to an epidemiological study by Byung on South Korean fencers, 47.2% of the total injuries recorded were lower extremity injuries, and knee injuries were among the most common [3]. Furthermore, based on a documentary analysis study conducted on athletes who are members of the training camp for the XVII Indonesian National Sports Week DKI Jakarta Provincial Team, the prevalence of injuries increased within three years from 2009-2012 in line with the addition of sports to the training program and increased training intensity [4]. In another study, Junaidi found that 30% of DKI Jakarta athletes participating in the XIX Indonesia National Sports Week suffered injuries.…”
Section: Introductionmentioning
confidence: 99%